Clinical Trials of Adult T-Cell Leukaemia/Lymphoma Treatment. (14th February 2012) - Marçais, Ambroise; Suarez, Felipe; Sibon, David; Bazarbachi, Ali; Hermine, Olivier
Abstract : Adult T-cell leukaemia/lymphoma (ATLL) is an aggressive malignancy of mature activated T cells caused by human T-cell lymphotropic virus type I (HTLV-1). Prognosis is severe because of intrinsic chemoresistance and severe immuosuppression. Four different subtypes are described with different outcomes, and treatment strategies vary according to the different clinical courses. Japanese trials show that combinations of chemotherapy can increase the response rates especially in the lymphoma subtype. However, patients have a high rate of relapse and the outcome remains extremely poor. Recently, a worldwide meta-analysis demonstrated that the combination of Zidovudine and Interferon-alpha (IFN) is effective in the leukemic subtypes (smoldering, chronic, and acute) and influences favorably the course of the disease. In order to prevent relapse, clinical trials testing new drugs such as monoclonal antibodies or combinations such as arsenic/IFN are needed. Finally, allogeneic stem cell transplantation is a feasible option but bears a very high rate of complications.